Estimating the effects of risk transfer mechanisms against floods in Europe and USA: A dynamic panel approach - Paul A. Raschky (University of Innsbruck, Department of Public Finance, 2007)
An analysis of the effects of natural hazards on society does not solely depend on a region's topographic or climatic exposure to natural processes, but the region's institutional resilience to natural processes that ultimately determines whether natural processes result in a natural hazard or not. An appropriate method for an international institutional comparison in the field of natural hazard management is still missing. The focus in this paper is on the institutional comparison of societal risk transfer mechanisms mitigating the effects disasters. Dynamic panel estimates using growth data from a) 199 European regions (NUTSII) between 1990-2004 and b) 3.050 U.S. counties between 1970-2003 reveal a significant negative impact of historical flood events on regional economic development. The application of GIS-data on the spatial distribution of flood events further allows to control for a regions exposure to floods. In the short run, a major flood event in a European region reduces the regional GDP by 0.4%-0.6%; an average flood event in the U.S.A reduces the personal income by 0.3%-0.4%. Mandatory insurance regimes in Europe absorb the negative short-run effect of a flood, while the National Flood Insurance Program (NFIP) in the U.S.A. mitigate the effects of a flood by about 50%. The results provide empirical foundation for the proposition that ex ante risk transfer policies are more efficient than ex post disaster relief.
Keywords: G22; Q54; R11; 330; natural hazards; growth; insurance; dynamic panel GMM; Naturkatastrophe; Risikopräferenz; Elementarschadenversicherung; Wirtschaftswachstum; Schätzung; Europa; USA